Activation of thousands of genes in the lungs and kidneys by sepsis is countered by the selective nuclear blockade - Qiao, Huan; Zienkiewicz, Jozef; Liu, Yan; Hawiger, Jacek (Frontiers in Immunology, 2023)
The steady rise of sepsis globally has reached almost 49 million cases in 2017, and 11 million sepsis-related deaths. The genomic response to sepsis comprising multi-system stage of raging microbial inflammation has been reported in the whole blood, while effective treatment is lacking besides anti-microbial therapy and supportive measures. Here we show that, astoundingly, 6,237 significantly expressed genes in sepsis are increased or decreased in the lungs, the site of acute respiratory distress syndrome (ARDS). Moreover, 5,483 significantly expressed genes in sepsis are increased or decreased in the kidneys, the site of acute injury (AKI). This massive genomic response to polymicrobial sepsis is countered by the selective nuclear blockade with the cell-penetrating Nuclear Transport Checkpoint Inhibitor (NTCI). It controlled 3,735 sepsis-induced genes in the lungs and 1,951 sepsis-induced genes in the kidneys. The NTCI also reduced without antimicrobial therapy the bacterial dissemination: 18-fold in the blood, 11-fold in the lungs, and 9-fold in the spleen. This enhancement of bacterial clearance was not significant in the kidneys. Cumulatively, identification of the sepsisresponsive host's genes and their control by the selective nuclear blockade advances a better understanding of the multi-system mechanism of sepsis. Moreover, it spurs much-needed new diagnostic, therapeutic, and preventive approaches.